THE IMPLEMENTATION OF LEARNING PROCESS AND LEARNING OUTCOMES ASSESSMENT OF MBKM PARTICIPANTS - Sri Sukarni; Pyo Apriliana Munawarah (Program Studi PGSD Universitas Flores, 2025)
Merdeka Belajar Kampus Merdeka (MBKM) is implemented in universities provides opportunities for students to study outside their study programs and campuses. This program encourages autonomous and flexible learning, so that students can achieve learning outcomes more innovatively. To achieve the expected goals both learning process and learning outcomes assessment that run optimally are required. Therefore, this study aimed to describe the implementation of : 1) learning process for craft and graphic arts for MBKM participants; 2) assessment of learning outcomes for craft and graphic arts for MBKM participants. This research used qualitative descriptive method. The participants of this study were all students who programmed MBKM in fine arts study program of FBMB Mandalika University of Education in the academic year 2024/2025. Data were obtained through observation, interviews, and documentation. It is found that the steps of learning process, are a) pre learning activities; b) learning activity or process of creating craft art and graphic art; c) finishing work of art. The aspects to be assessed in graphic art assessment, namely: a) technique; b) material; c) design; d) function and e) aesthetics. The aspects to be assessed in craft art assessment namely a) idea; b) technique/media; c) creativity. The implication of learning process and assessment are the students’ art work combined aesthetic and functional elements in everyday objects.